Gender wage-productivity differentials and global integration in China - Ana C. Dammert; Beyza Ural Marchand; Chi Wan (Institute for the Study of Labor (IZA), 2013)
In the absence of discrimination, there should be no wage-productivity differentials as relative wages should be equal to the relative marginal productivity levels of workers. This paper investigates the role of globalization on the structure and evolution of gender differentials in China by simultaneously estimating demand-side wage and productivity outcomes using nonlinear least squares. The analyses are based on a comprehensive population-wide panel survey of manufacturing firms between the years of 2004 and 2007, covering 94 percent of total industry output and providing an accurate representation of labor demand. The results suggest that more exposure to globalization through increased exports is associated with lower gender wage-productivity differentials, and more exposure through increased foreign investment leads to differentials in favor of female workers. On the other hand, gender discrimination is found to be prevalent among domestically owned and non-exporting firms.
Keywords: D22; F21; F61; J16; J31; 330; China; gender wage discrimination; globalization; firm ownership